l Congresso Internazionale “La grandezza della vita quotidiana” (2002) / The International Congress “The Grandeur of Ordinary life” - Miguel Ángel Ortiz (Studia et Documenta)
In January 2002, for the celebration of the centennial of the birth of St. Josemaría, an international congress with the title “The Grandeur of Ordinary Life” took place. The publication of the event, in fourteen volumes, gives us an idea of the richness of the reflections, developed in nine reports, more than a hundred communications and in eighteen workshops. With different perspectives and methods, the material that this article presents has permitted us to grasp the force of the foundation light that St. Josemaría received.